Body work in health and social care : critical themes, new agendas - Twigg, Julia (Malden, MA : Wiley-Blackwell, 2011)
'The first book to fully explore the multiple ways in which body work features in health and social care and the meanings of this work both for those employed to do it and those on whose bodies they work. Explores the commonalities between different sectors of work, including those outside health and social care Contributions come from an international range of experts Draws on perspectives from across the medical, therapeutic, and care fields Incorporates a variety of methodological approaches, from life history analysis to ethnographic studies and first person accounts'--
'Body work is paid work undertaken on the bodies of others. Although it forms a central part of health and social care, its study has often been obscured or neglected. This volume is the first to directly address the concept, exploring the multiple ways in which body work features in health and social care and analyzing the meanings of this work for both those employed to do it and those on whose bodies they work. With contributions from the top international scholars in the field, the book draws on perspectives from across the medical, therapeutic, and care fields. Using a variety of methodological approaches, from life history analysis to ethnographic studies and first person accounts, this book highlights the embodiment of health and social care and the contribution of this emphasis to new directions in sociology.'--
Machine generated contents note: 1. Conceptualising body work in health and social care (Julia Twigg, Carol Wolkowitz, Rachel Lara Cohen and Sarah Nettleton). 2. Time, space and touch at work: body work and labour process (re)organisation (Rachel Lara Cohen). 3. Managing the body work of home care (Kim England and Isabel Dyck). 4. The means of correct training: embodied regulation in training for body work among mothers (Emma Wainwright, Elodie Marandet and Sadaf Rizvi). 5. From body-talk to body-stories: body work in complementary and alternative medicine (Nicola Kay Gale). 6. Educating with the hands: working on the body⁄self in Alexander Technique (Jennifer Tarr). 7. Treating women's sexual difficulties: the body work of sexual therapy (Thea Cacchioni and Carol Wolkowitz). 8. Actions speak louder than words: the embodiment of trust by healthcare professionals in gynae-oncology (Patrick R. Brown, Andy Alaszewski, Trish Swift and Andy Nordin). 9. Body work in respiratory physiological examinations (Per Måseide). 10. In a moment of mismatch: overseas doctors' adjustments in new hospital environments (Anna Harris). 11. The co-marking of aged bodies and migrant bodies: migrant workers' contribution to geriatric medicine in the UK (Parvati Raghuram, Joanna Bornat and Leroi Henry). 12. Afterword: Body work and the sociological tradition (Chris Shilling).
Includes bibliographical references and index.
Keywords: Human body -- Social aspects; Social medicine